Cervical cancer screening programs for female sex workers: a scoping review - Vimpere, Léa; Sami, Jana; Jeannot, Emilien (Frontiers in Public Health, 2023)
Background Cervical cancer (CC) is the fourth most common neoplasia affecting women worldwide. Female sex workers (FSWs) are among those at highest risk of developing and succumbing to CC. Yet, they are often overlooked in CC screening programs and have limited access to CC healthcare globally. The development of CC screening programs for this high-risk target population is necessary to reduce the global burden of this disease and to reach the World Health Organization’s objective of accelerating the elimination of CC. Objective This review summarizes findings on CC screening programs for FSWs that have been implemented worldwide, and assesses their effectiveness and sustainability. Methods A scoping review was conducted using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). A literature search was performed on PubMed, Swisscovery, and Google Scholar for studies describing and assessing CC screening programs for FSWs. In addition, targeted searching online Non-Governmental and International Organizations websites identified grey literature. A single reviewer screened titles and abstracts, and extracted data from the research findings. Results The search identified 13 articles published from 1989 to 2021. All implemented programs successfully reached FSWs and provided them with CC screening during the study period. The most effective and sustainable strategies were the Screen and Treat approach, introducing CC screening into existing STI services in drop-in or outreach clinics, HPV-DNA self-sampling, and integrating sex-workers-specific services in public health facilities. Follow-up was deemed the main challenge in providing and enhancing CC healthcare to FSWs with rates of loss to follow-up ranging from 35 to 60%. Conclusion FSWs are often omitted in national CC screening programs. The further development and improvement of CC healthcare, including follow-up systems, for this high-priority target population are imperative.